Disease activity at two consecutive registry visits and subsequent medication escalation for patients with juvenile idiopathic arthritis in the CARRA registry - Melissa L. Mannion; Monica S. Aswani; K. Ria Hearld; Emily A. Smitherman; Livie Timmerman; Jeffrey R. Curtis; for the CARRA Registry Investigators (Pediatric Rheumatology Online Journal)
Abstract Objective To account for the chronic time course of juvenile idiopathic arthritis (JIA), we assessed medication changes by disease activity patterns across 2 sequential timepoints. Methods Patients with non-systemic JIA enrolled in the Childhood Arthritis and Rheumatology Research Alliance Registry with complete clinical Juvenile Arthritis Disease Activity Scores (cJADAS) at 6 and 12-month registry visits were included. Disease activity was classified by cJADAS categories (inactive/minimal, moderate/high). The primary outcome was disease modifying anti-rheumatic drug (DMARD) escalation at the 12-month visit. We examined the association between cJADAS patterns and DMARD escalation. Results The cJADAS patterns across paired visits for 2,956 patients with JIA were: 71% persistent inactive/minimal, 25% persistent moderate/high, 2% “improving”, and 2% “flaring”. Only 10% of patients had DMARD escalation at the 12-month visit, including only 15% of patients with persistent moderate/high disease activity. In multivariable logistic regression adjusting for sociodemographic and clinical variables, DMARD escalation at the 12-month visit was associated with “flaring” disease activity (odds ratio [OR] 2.62, 95% confidence interval [CI] 1.33–5.18), DMARD escalation between the 6- and 12-month visits (OR 1.86, 95% CI 1.40–2.49) and morning stiffness (> 60 min 4.98, 95% CI 3.00–8.27), while age 15–19 years were less likely to escalate (OR 0.61, 95% CI 0.38–0.97). Conclusion In a large multicenter registry of US patients with JIA, DMARD escalation at the 12-month visit was uncommon overall, even for those with persistent moderate/high disease activity. Our findings suggest that DMARD escalation in this cohort did not align well with a treat to target approach using cJADAS thresholds.